2014
DOI: 10.1073/pnas.1415330111
|View full text |Cite
|
Sign up to set email alerts
|

Substratum-induced differentiation of human pluripotent stem cells reveals the coactivator YAP is a potent regulator of neuronal specification

Abstract: Physical stimuli can act in either a synergistic or antagonistic manner to regulate cell fate decisions, but it is less clear whether insoluble signals alone can direct human pluripotent stem (hPS) cell differentiation into specialized cell types. We previously reported that stiff materials promote nuclear localization of the Yes-associated protein (YAP) transcriptional coactivator and support long-term self-renewal of hPS cells. Here, we show that even in the presence of soluble pluripotency factors, complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
177
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(183 citation statements)
references
References 49 publications
6
177
0
Order By: Relevance
“…Murphy et al recently reviewed the significance of the mechanical properties of ECM in determining stem cell fate [173]. composition in hiPSC-derived neural cultures has also been shown [174]. Altogether, one could recreate the necessary mechanical properties (elasticity and stiffness) [175,176], relative cellular positioning, vascular innervations, and morphogen gradients characteristic of in vivo neural development [177].…”
Section: Miniature Three-dimensional Tissue Assemblies Called Organoimentioning
confidence: 99%
“…Murphy et al recently reviewed the significance of the mechanical properties of ECM in determining stem cell fate [173]. composition in hiPSC-derived neural cultures has also been shown [174]. Altogether, one could recreate the necessary mechanical properties (elasticity and stiffness) [175,176], relative cellular positioning, vascular innervations, and morphogen gradients characteristic of in vivo neural development [177].…”
Section: Miniature Three-dimensional Tissue Assemblies Called Organoimentioning
confidence: 99%
“…In spite of the above mentioned challenges, improvements for iPSC differentiation to neural cells and tissues are being made through the development of better defined, optimised and efficient protocols[30, [99][100][101][102][103], bolstered by increased availability of superior stem cells attributable to improved somatic cell reprogramming, stem cell culture, banking and distribution [104][105][106][107]. A major advance from traditional differentiation methods is the circumvention of embryoid body (EB) formation for more efficient and direct induction of neural progenitor cells (NPCs) and expansion of neurospheres [99][100][101][102].…”
Section: Neural Differentiation Of Ipscs: Quality and Quantitymentioning
confidence: 99%
“…A fourth and most recent method by Musah et al represents a different approach to neuronal induction by using substratum mechanics rather than soluble signalling factors to regulate neuronal specification from iPSCs [103]. Consistent with advances in biomaterials based cell support and tissue engineering (see below section), whereby physical and other non-chemical stimuli are increasingly being applied to regulate cell fate, Musah and colleagues use hydrogels with elasticity similar to brain tissue to rapidly and efficiently differentiate iPSCs to neurons.…”
Section: Neural Differentiation Of Ipscs: Quality and Quantitymentioning
confidence: 99%
“…37 Similarly, neuronal specification (i.e., GABAergic interneurons) of hPSCs was enhanced in the absence of neurogenic factors on soft substrates (0.7 kPa vs. 3-10 kPa) that inhibited the nuclear localization of YAP. 38 While these studies were performed in 2-D cultures, inhibition of nuclear YAP for neural differentiation of hPSCs based on 3-D cultures remains to be revealed.…”
mentioning
confidence: 99%
“…Musah et al, 2014 [38] (Continued on next page) YAP/TAZ is found to be related to the interactions between Hippo signaling and the Rho GTPase signaling. 40 Stress fibers reduce YAP phosphorylation and promote nuclear YAP accumulation, 41 so disruption of stress fibers using cytochalasin D reduces nuclear YAP.…”
mentioning
confidence: 99%